2017
DOI: 10.1105/tpc.17.00452
|View full text |Cite
|
Sign up to set email alerts
|

ABA-Induced Stomatal Closure Involves ALMT4, a Phosphorylation-Dependent Vacuolar Anion Channel of Arabidopsis

Abstract: Stomatal pores are formed between a pair of guard cells and allow plant uptake of CO 2 and water evaporation. Their aperture depends on changes in osmolyte concentration of guard cell vacuoles, specifically of K + and Mal 22 . Efflux of Mal 22 from the vacuole is required for stomatal closure; however, it is not clear how the anion is released. Here, we report the identification of ALMT4 (ALUMINUM ACTIVATED MALATE TRANSPORTER4) as an Arabidopsis thaliana ion channel that can mediate Mal 22 release from the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 76 publications
(104 reference statements)
0
67
0
Order By: Relevance
“…Members of ALMT clade 2 (ALMT3/4/5/6/9) including the pollen expressed ALMT3/4/5 (Fig. c) are targeted to the vacuolar membrane (Meyer et al ., ; De Angeli et al ., ; Zhang, ; Eisenach et al ., ) and were thus not considered in our studies for contributing to plasma membrane anion currents.…”
Section: Resultsmentioning
confidence: 99%
“…Members of ALMT clade 2 (ALMT3/4/5/6/9) including the pollen expressed ALMT3/4/5 (Fig. c) are targeted to the vacuolar membrane (Meyer et al ., ; De Angeli et al ., ; Zhang, ; Eisenach et al ., ) and were thus not considered in our studies for contributing to plasma membrane anion currents.…”
Section: Resultsmentioning
confidence: 99%
“…AtALMT6 mediates Ca 2+ and pH-dependent malate currents into guard cell vacuoles (Meyer et al, 2011). Most recently, another tonoplast-targeted ALMT channel, AtALMT4, was shown to mediate malate efflux from vacuoles, functioning in stomatal closure in response to ABA (Eisenach et al, 2017). Interestingly, not only is malate transported into vacuoles by ALMT9, but cytosolic malate and oxaloacetate also up-regulate the ALMT9 channels that reside in the vacuolar membrane of guard cells and other plant cells, with ALMT9 channel activation occurring at c. 0.3 mM cytosolic malate (De .…”
Section: Researchmentioning
confidence: 99%
“…VvALMT9 is a homolog of AtALMT9 in grape (Vitis vinifera L.) and reportedly controls the acidity of berries during fruit maturation by facilitating tartrate, malate and succinate accumulation in the vacuoles of mesocarp cells [15]. A recent study also indicated that the ABA induced anion channel AtALMT4 of mediates Mal 2− efflux from the vacuole during stomatal closure and its activity depends on phosphorylation [38].…”
Section: Almt Genes Perform Various Functions Among Plantsmentioning
confidence: 99%
“…Reconstituting the active channel in almt4 mutants impaired growth and stomatal opening. Phosphomimetic mutants were electrically inactive and phenocopied the almt4 mutants and S382 can be phosphorylated by mitogen-activated protein (MAP) kinases in vitro [38]. Therefore the residues might be more important to tertiary protein structure rather than specifically involved with the activation by Al [73].…”
Section: The Structure-function Relationship Of Almt Proteinsmentioning
confidence: 99%
See 1 more Smart Citation